Social Mapping in the Development of Border Area: Case Study of Batu Ampar Village - Sayed Fauzan Riyadi (Kemudi, 2023)
Social mapping is something important to do before empowering society. The activities of dedication to society are identified with various potential and problems that exist in society. The purpose of this service activity is to map the actors, potential and problems that exist in the village of Batu Ampar in the Anambas Islands. The results of the dedication, based on the data obtained on social maps in the village of Batu Ampar, are analyzed on the interaction between actors involved both individuals and sufficiently good organizational groups that are dominated by interactions that are associative or relationships that potentially produce cooperation and synergies.